2019
DOI: 10.1212/wnl.0000000000007091
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of LDL-C on ischemic stroke and coronary disease

Abstract: Objective To examine the causal relevance of lifelong differences in low-density lipoprotein cholesterol (LDL-C) for ischemic stroke (IS) relative to that for coronary heart disease (CHD) using a Mendelian randomization approach. Methods We undertook a 2-sample Mendelian randomization, based on summary data, to estimate the causal relevance of LDL-C for risk of IS and CHD. Information from 62 independent genetic variants with genome-wide significant effects on LDL-C lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 45 publications
(57 reference statements)
5
47
1
Order By: Relevance
“… 14 Complementing these observational associations, in findings from genetics consortia, genetically elevated LDL-C levels were associated with a higher risk of large artery stroke but not consistently with a risk of small artery stroke or cardioembolic stroke; however, more data are needed to reliably confirm these distinctions. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“… 14 Complementing these observational associations, in findings from genetics consortia, genetically elevated LDL-C levels were associated with a higher risk of large artery stroke but not consistently with a risk of small artery stroke or cardioembolic stroke; however, more data are needed to reliably confirm these distinctions. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilized this method to investigate the role between PUFA and IS. Additionally, lipids and blood pressure were the main modifiable factors of IS [4,[34][35][36][37]. So, we extended the objectives to these factors (LDL-C, HDL-C, TC, SBP and DBP).…”
Section: Introductionmentioning
confidence: 99%
“…These findings contradict the results of Roy-O'Reilly et al, which claimed that either age or LDL-C factors dominated the carotid stenosis. [14][15][16] The IPA capability of integrating individual factors with their probable cross-interaction improved the program convergence and yielded a high value of r 2 ¼ 0:9352.…”
Section: Resultsmentioning
confidence: 99%
“…14 (2) LDL-C. Epidemiologists have reported that LDL-C level strongly promoted carotid stenosis in elderly patients with cerebral infarction. 15,16 (3) MAP. This is the mean pressure per one complete cardiac cycle in human arteries, which indicates the perfusion to organs more clearly than systolic or diastolic blood pressures (SBP and DBP, respectively: MAP ¼ ðSBP þ 2 Á DBPÞ=3.…”
Section: -4mentioning
confidence: 99%